Technology transfer by multinationals - Hatti, Neelambar 1940-.; Singer, Hans Wolfgang 1910-.; Tandon, Rameshwar IV.Title. (New Delhi Ashish Pub. House, 1988)
Contributed articles.
Keywords: Technology transfer; International business enterprises